Evaluation of penetration depth of 2% chlorhexidine digluconate into root dentinal tubules using confocal laser scanning microscope - Sekar Vadhana; Jothi Latha; Natanasabapathy Velmurugan (Korean Academy of Conservative Dentistry, 2015)
Objectives This study evaluated the penetration depth of 2% chlorhexidine digluconate (CHX) into root dentinal tubules and the influence of passive ultrasonic irrigation (PUI) using a confocal laser scanning microscope (CLSM). Materials and Methods Twenty freshly extracted anterior teeth were decoronated and instrumented using Mtwo rotary files up to size 40, 4% taper. The samples were randomly divided into two groups (n = 10), that is, conventional syringe irrigation (CSI) and PUI. CHX was mixed with Rhodamine B dye and was used as the final irrigant. The teeth were sectioned at coronal, middle and apical levels and viewed under CLSM to record the penetration depth of CHX. The data were statistically analyzed using Kruskal-Wallis and Mann-Whitney U tests. Results The mean penetration depths of 2% CHX in coronal, middle and apical thirds were 138 µm, 80 µm and 44 µm in CSI group, respectively, whereas the mean penetration depths were 209 µm, 138 µm and 72 µm respectively in PUI group. Statistically significant difference was present between CSI group and PUI group at all three levels (p < 0.01 for coronal third and p < 0.001 for middle and apical thirds). On intragroup analysis, both groups showed statistically significant difference among three levels (p < 0.001). Conclusions Penetration depth of 2% CHX into root dentinal tubules is deeper in coronal third when compared to middle and apical third. PUI aided in deeper penetration of 2% CHX into dentinal tubules when compared to conventional syringe irrigation at all three levels.